Anchors for Effectors: Subversion of Phosphoinositide Lipids by Legionella - Hilbi, Hubert; Weber, Stephen; Finsel, Ivo (Frontiers in Microbiology, 2011)
The facultative intracellular pathogen Legionella pneumophila replicates in free-living amoebae and macrophages within a distinct compartment, the “Legionella-containing vacuole” (LCV). LCV formation involves phosphoinositide (PI) glycerolipids, which are key factors controlling vesicle trafficking pathways and membrane dynamics of eukaryotic cells. To govern the interactions with host cells, L. pneumophila employs the Icm/Dot type IV secretion system and more than 250 translocated “effector proteins” that presumably subvert host signaling and vesicle trafficking pathways. Some of the effector proteins anchor through distinct PIs to the cytosolic face of LCVs and promote the interaction with host vesicles and organelles, catalyze guanine nucleotide exchange of small GTPases, or bind to PI-metabolizing enzymes, such as OCRL1. The PI 5-phosphatase OCRL1 and its Dictyostelium homologue Dd5P4 restrict intracellular growth of L. pneumophila. Moreover, OCRL1/Dd5P4, PI 3-kinases (PI3Ks), and PI4KIIIβ regulate LCV formation and localization of the effector protein SidC, which selectively decorates the LCV membrane. SidC and its 20-kDa “P4C” fragment are robust and specific probes for phosphatidylinositol-4-phosphate, and SidC can be targeted to purify intact LCVs by immuno-magnetic separation. Taken together, bacterial PI-binding effectors as well as host PIs and PI-modulating enzymes play a pivotal role for intracellular replication of L. pneumophila, and the PI-binding effectors are valuable tools for the analysis of eukaryotic PI lipids.